B92 Audit on conduct of regional anaesthesia: baseline evaluation of department's practice. (11th August 2022) - Patil, A; Mehta, M
Abstract : Background and Aims: The Royal College of Anaesthetists (RCOA) and the Association of Anaesthetists of Great Britain and Ireland have laid down the best practice standards for the conduct of regional anaesthesia (RA) 1, 2 . We performed a baseline evaluation of our Department's practice against these 1–3 . Methods: A questionnaire was devised based on the standards set out by the RCOA and AAGBI 1, 2 . This included the following- 1) Whether patients had working IV access prior to commencing a block 2) If appropriate monitoring was commenced, and 3) If the "Stop Before You Block (SBYB)" safety check was performed immediately prior to needling. The questionnaires were completed after the block. We focussed on the trauma and orthopaedic procedures (emergency and elective), looking at unilateral blocks. The anaesthetists were notified beforehand to gainconsent. Results: Thirty questionnaires were collected over one month. All patients had working intravenous access. Monitoring was done in all patients except one sedated patient, when ETCO2 was not used. SBYB was performed in all cases, but not documented in 20%. A SBYB box was used to store prepared drugs in all but one case. Conclusions: Our compliance is overall encouraging, as recommended safety nets are extremely important to prevent 'never events' 1 . One limitation was the potential bias as questionnaire were done by team assisting the block. Our Department uses a dedicated SBYB prepbox, in line with the new 'Prep, Stop, Block' guidelines 4 . Use of ETCO2 is recommended in patients having block under sedation or GA 2 . We aim to repeat audit next year.